Sürdürülebilir Şehirleşme Ve Toplu Konut Projelerinde Etkin Enerji Kullanımı - Özügül, Mehmet Doruk (Fen Bilimleri Enstitüsü, 1998)
Sanayi devrimini takiben, ufak çaptaki çevre kirliliklerinin yerini global veya bölgesel kirlenme veya tahriplere bırakmasıyla ve ciddi kaynak darboğazları sonucunda "Sürdürülebilir Kalkınma" birçok gelişmiş ve gelişmekte olan ülkenin hedefi haline gelmiştir. Sürdürülebilir Kalkınma veya Sürdürülebilir Şehirleşme kısa vadede, izole olarak veya toplumun bir kesimi tarafından benimsenerek erişilebilecek hedefler değildir. Toplumun kendi içinde, ülkeler ve uluslar arasında ve kurumlar arasında bir eşgüdüm sürdürülebilirlik bilincinin oluşması ve uygulamaya geçebilmesi için şarttır. "Sürdürülebilir Kalkınma'nın", yapılaşmış çevreye indiği, fonksiyon bölgelerinin (özellikle konut alanlarının), konutların doğaya uygun olarak tasarlandığı ve sürdürülebilirlik fikrine hizmet ettiği boyutu "Sürdürülebilir Şehirleşme" 'dir. Sürdürülebilir Kalkınma bir neslin ihtiyaçlarını, kendinden sonra gelen nesillerin kendi ihtiyaçlarını giderme ve yaşama şansını yok etmeden gidermesidir. Bu tezin amacı; Sürdürülebilir Şehirleşme için enerji kaynaklarının etkin kullanımı, yenilenebilir enerji kaynaklan, doğaya uygun yapılaşma konularına çeşitli boyutlarda ve örneklerle eğilmek ve ülkemizdeki durumu 5 toplu konut alanını esas alarak incelemektir. Sekiz bölümden oluşan çalışmanın birinci bölümünde konu ana hatlarıyla anlatılmış, ikinci bölümde sürdürülebilirliğin tarihçesi, tanımı, boyutları ve eksikleri üzerinde durulmuş, üçüncü bölümde Sürdürülebilir Şehirleşme' nin Şehir Ekolojisi ile ilişkisi ve Şehir Ekolojisi'nin tanımı ele alınmış, dördüncü bölümde Sürdürülebilir Kalkınma ve Ekolojik Planlama'nın fiziksel mekana yönelik yönleri üzerinde durulmuş, beşinci bölümde enerjinin etkin kullanımı, yenilenebilir enerji kaynaklan ve geri kazanım incelenmiş, altıncı bölümde örnekler verilmiş, yedinci bölümde Ataşehir, Bahçeşehir, Halkalı, Mimaroba ve Sinanoba'da kullanıcı anketleri, teknik personel anketleri, doğal yapı analizleri ve şahsi araştırmalarla elde edilen bilgiler açıklanmış ve sonuçlar ortaya konmuş, sekizinci bölüm olan sonuçlar ve öneriler bölümünde çalışmanın sonuçları ve öneriler genel bir değerlendirme çerçevesinde ortaya konmuştur.

Sustainable development and efficient use of resources are very important subjects concerning continuity of life on earth. Cities and human beings are main consumers of nature. Human beings use the resources of nature without thinking that the resources are finite. Especially in the developed countries many researches are made about sustainable settlements. There are a lot of subjects when a sustainable settlement is thought and also there is not a certain settlement template which can be called sustainable. But architects and city planners have very important missions like protecting the nature, giving minimum harm to the environment, investigating and using renewable resource types in their projects, causing the least necessity of using extra energy and recycling resources. The aim of this thesis is analyzing the situation in the world and especially in Turkey about sustainability and efficient use of energy in the new housing projects. In the first part of the research the general structure, parts and the aim of the thesis are explained briefly. In the second part of the thesis the history, definitions and scales of sustainability and criticisims related to sustainable development, are explained. Since 1970' s, sustainable development has been one of the major topics which is related to environmental problems and their solutions. Two different strategies about sustainability have been observed in history. The first strategy is "react and cure" strategy which assumes that development brings environmental problems and dirt and it is unavoidable. According to this strategy the only thing which could be done is solving problems after they occur. React and cure strategy says that trying to prevent the problems is unnecessary. In time the second strategy developed and it was called "anticipate and prevent" strategy. Predicting the problems before they xm exist and preventing them is the main aim of this strategy. As people understand that the environmental problems are vital, it is thought that sustainability is a serious and essential subject. There are lots of different definitions of sustainable development, but as a common definition, sustainable development is answering today's needs without destroying tomorrow's. Mainly sustainability is analysed at three scales. These scales are necessary but they may not be sufficient (Especially there is a lack about the consumption habits of the society in these scales). They are: a) Global Sustainability. b) Regional Sustainability. c) Local Sustainability. For global sustainability, comparing to the authority of a country, an international organization, having much more authority on the consumption of the resources, environmental problems and threats is needed. Worldwide rights must be more important than the rights of the countries, and the only way of obtaining this is to costitute an international organization. Regional sustainability is an intermediate (meso) scale between global (macro) and local (micro) scales. Regional scale is a better scale to control and direct a sustainable system, because this scale is much more aware of the resource regions and their unique characters. Local sustainability is the scale in which the global and regional decisions are applied. It is a more detailed scale. The biggest criticism against sustainability is its indefinite property. And also some criticisms claim that "development" (sustainable development) cannot be thought without pollution. In the third part of the thesis sustainable urbanization and urban ecology are compared and urban ecology is explained. According to urban ecology and "natural selection" rule, the groups possessing the strongest economic resources will win in the struggle for the best and the most expensive sites. So equal activities and equal individuals are sorted to equal XIV (same) areas. This process is explained by ecological terms such as "dominance", "invasion" and "succession". But sustainability tries to divide and share the resources on the world equally and sustainable urbanization aims to make every individual equal and tries to give them equality of opportunity. According to the viewpoint of urban ecology, strong gets what he wants in a city. "Equality of opportunity" goal of sustainability could be explained by the viewpoint of urban ecology. In the fourth part of the research, sustainable neighbourhoods and the principles of ecological building (building within the sensitivity of thinking nature) are pointed out. Being multi-disciplined is one of the major factors of sustainable neighbourhoods. For sustainable neighbourhoods, technical approach, sociological approach, experimental design approach and political approach must be thought in coordination. There are two main ideas about ecological housing. One of them is building one story, traditional houses constructed with the help of local materials and the other idea is searching the best type of housing for the site with the help of technological developments. In the fifth part, effective use of energy, renewable energy resources and recycling are the main subjects. Effective use of energy includes Combined Heat And Power systems (CHP) and District Heating (DH). Space and water heating and space cooling are the subjects which had better think with orientation and situation of the buildings. Space and water heating is related with the situation of the building according to the movement of the sun and wind. Minimizing the lost heat is one of the main topics in space and water heating. CHP systems must be used for efficient heating of the all buildings in a settlement. Also isolation is one of the important principles about efficient heating. Space cooling and heating are also related with the design and construction preventations of a building. For greater savings, machines (washing machine, tap etc.) used in houses should consume less energy (or resource). XV With the right organizations obtaining sunlight for the house, use of artificial light could be reduced. Transportation is one of the essential subjects about efficient use of energy. Riding a bicycle and walking are called habits that respect energy consumption. Solar energy, wind and stream energy, geothermal energy and biomass are determined as renewable resources. Especially solar energy and solar design are very widespread and well known. Solar energy production could be seperated to two topics according to the energy production technique: they are active solar design and passive solar design. In active solar design some apparatus are used in order to produce solar energy (like flat plate), passive solar design is the one which aims to get maximum sunlight in winter and minimum sunlight in summer. In active solar design location of the collector is very important. Obtaining geothermal energy, wind and stream energy and biomass need their own special conditions and they are all very expensive systems. Using geothermal energy is generally heating water, with the help of underground hot rocks and heating spaces by this hot water transfered by pipes. It is possible to create energy by wind and stream turbines. The continuity of the wind and stream is the most important point when such a system is settling. Wind and stream turbines also have some harms to the nature. A wind turbine could make noise, cause a bad visual effect and could be on the migration route of the birds. A stream turbine could damage some type of animals living in the coasts like mussels. And biomass produces heat with the help of prophane gained from the animals. Recycling both the solid wastes and water are very important for sustainability. Especially paper, glass, organic wastes and metal pieces could be easily recycled as solid wastes. This is an economic way of production. After filtration, rain and dirty water (residential) could be used in irrigation. In the sixth part, 11 examples concerning sustainable are given from 5 different country. Examples are all related with sustainability. Especially Oak Hills is a very good example in which energy plan is developed also with orientation and wind control decisions. In the seventh part of the thesis, (Ataşehir, Bahçeşehir, Halkalı, Mimaroba and Sinanoba) 5 mass housing projects are investigated with the questionaires applied to XVI the staff and users. Also slope, orientation, wind and river basins of the sites are analysed. Except Ataşehir all the other new housing projects are on the European part of Istanbul. According to all of the investigations, wind and orientation are not within the factors that are paid attention. In these settlements slope is considered as a very important factor for the constructor firms and river basins of the sites are also quite important. Public transport, bicycle roads and main pedestrian roads are essential for energy use in transportation. Two of the five mass housing projects have no connection (Mimaroba and Sinanoba) with a public transport system and only one of them have bicycle road. (Ataşehir) Again only two of the sites have main pedestrian roads. (Ataşehir and Halkalı) There are no conscious energy saving regulations about transportation, but according to the user questionaires altough most all of the families have private cars, people prefer to go to the centers by walking. Showing that there is an important relation between the average of the distances from buildings to the nearest center and walking preferences (in each new housing projects), a correlation of -0.6239 is calculated. In most of the settlements rain and dirty water (Bahçeşehir, Mimaroba and Sinanoba) are recycling. They are mostly used for irrigation. None of the sites pay attention solar energy, wind energy, CHP(Combined Heat And Power), geothermal energy and biomass. Solid wastes are collected in a well-organized way, but they are not recycled in local level. When the orientation of placesin houses are analyzed, %25 of the houses have places towards north, %33.3 of them have places towards west and %25 of them have places towards east. There is a correlation of, 0.6338 between the places towards north and the places that users are complained, and 0.7532 between the places towards northeast and the places that users are complained. So it could be said that places towards north and northeast cause the most heat loss in the analysed houses. Preventing the heat loss, places must be carefully oriented towards north and northeast, especially rooms used oftenly mustn't be towards north and northeast. Another way of preventing the heat loss is isolation, but it is expensive. In spite of XVU paying for isolation of a house, it is cheaper to design houses with minimum spaces towards north and northeast. Showing that cooling arrangements are not sufficient in the dwellings, %11.4 of the users paid for extra cooling machines and %5.2 of them added slatted shutters to their houses (%54.8 of the houses have slatted shutters from the beginning). The last part is the conclusion that points out the general tendencies concerning sustainable settlements and the position of the analysed new housing projects in Istanbul also with the help of the survey. The result of the thesis shows that the settlements analysed, have to pay more and more attention to energy consumption, recycling and renewable energy sources. Comparing to the new housing projects built in developed countries, observed new housing projects are in a worse position about the subject of sustainable settlements. During organizing, planning and constructing such kind of projects, related authorities must be more sensitive and conscious, about using the technology for the benfit of nature.
Sustainable Urbanization And Efficient Use Of Energy In Housing Projects
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Enerji; Kentleşme; Sürdürülebilir kalkınma yönetimi; Toplu konut projeleri; Energy; Urbanization; Sustainable development management; Mass housing projects